Caesar and the Lamb: Early Christian Attitudes on War and Military Service. By George Kalantzis - Daunton-Fear, Andrew (The journal of theological studies, 2014)
George Kalantzis is Associate Professor of Theology at Wheaton College, where he directs the Wheaton Center for Early Christian Studies. He has hitherto specialized in fourth- and fifth-century historical theology and is the author and editor of a number of books. In this study, however, he focuses on the pre-Nicene period, sifting the sources for information on early patristic attitudes to Christians and military service., Kalantzis says he has written with the general reader in mind and indeed he provides a monograph that will be found conveniently accessible to most readers. It consists of an extended introduction (chs. 1–4) followed by extracts in English from the relevant patristic writings (chs. 5–12), some translations being supplied by himself.